Initial Experience Performing Mechanical Thrombectomy With the CatchView Mini Device for Distal M2 Segment Middle Cerebral Artery Occlusions - Vega, Pedro; Murias, Eduardo; Jimenez, Jose María; Chaviano, Juan; Benavente, Lorena; Gonzalez-Delgado, Montserrat; García-Arias, Faustino; Pumar, José Manuel (Frontiers in Neurology, 2021)
Background: Mechanical thrombectomy (MT) has become the standard of care for acute ischemic stroke due to large vessel occlusion; however, its safety and efficacy in patients with distal strokes remains unclear. In this study, we investigated the safety and efficacy of MT for distal middle cerebral artery (MCA) occlusions using the CatchView Mini (CVM; Balt, Montmorency, France). Methods: This was a prospective single-center analysis of patients with a single MCA-M2 occlusion treated with the CVM device. Consecutive patients were prospectively enrolled from October 2018 to March 2020. Efficacy outcomes included successful recanalization [modified Thrombolysis in Cerebral Infarction (mTICI) 2b/3], procedure times, and number of device passes. Clinical outcomes included National Institutes of Health Stroke Scale Score (NIHSS) at discharge, 90-day functional independence (modified Rankin Scale 0–2) and safety outcomes included hemorrhagic complications, and 90-day mortality. Results: A total of 45 patients (mean age: 74.0 ± 12.6; 53.3% [24/45] female) were included in the study. Upon admission, 33.3% (15/45) of patients were mRS 3–5; and mean NIHSS was 13.2 ± 4.2 Mean time from symptom onset to final angiography was 250.0 ± 83.4 min with a mean intervention duration of 34.0 ± 12.6 min. The mean number of device passes was 1.8 ± 1.5 final mTICI 2b/3 was achieved in 91.1% (41/45) of patients. Eight hemorrhagic complications (17.8%, 8/34) occurred, none of which were symptomatic. At 90-days, 57.8% (26/45) patients were functionally independent and the rate of mortality was 15.6% (7/45). Conclusions: The present analysis demonstrates a low risk profile and high recanalization success for patients with distal M2 occlusions treated with the CVM device.